2020
DOI: 10.1088/1755-1315/473/1/012133
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the catchable size of orange-spotted grouper (Epinephelus coioides) in Kwandang Bay, Gorontalo Utara District, Indonesia

Abstract: The orange-spotted grouper (Epinephelus coioides) is a valuable food fish. To support the sustainable management of orange-spotted grouper fisheries, it is important to determine the optimum catchable size. The purpose of this study was to determine an optimal catchable size for the orange-spotted grouper stock in Kwandang Bay, North Gorontalo District, Indonesia. The Catchable size was determined based on the size at first sexual maturity, fecundity, and reproductive potential. The study was conducted from De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 23 publications
3
15
0
2
Order By: Relevance
“…Fecundity is considered the most reliable indicator to estimate fish reproductive potential (Bhatt and Pandit, 2015;Achmad et al, 2020). The estimates of mahseer fecundity in this research fall within the range of mahseer fecundity reported from other studies (Table IV).…”
Section: O N L I N E F I R S T a R T I C L Esupporting
confidence: 83%
“…Fecundity is considered the most reliable indicator to estimate fish reproductive potential (Bhatt and Pandit, 2015;Achmad et al, 2020). The estimates of mahseer fecundity in this research fall within the range of mahseer fecundity reported from other studies (Table IV).…”
Section: O N L I N E F I R S T a R T I C L Esupporting
confidence: 83%
“…Most of these fisheries face challenges, such as a lack of social-ecological data and poor management [8]. The previous studies, particularly in Indonesia, focus on these fisheries' biological and ecological perspectives [9]- [17].…”
Section: Introductionmentioning
confidence: 99%
“…Oleh karena itu, dilakukan penelitian yang fokus pada kajian sex ratio dan ukuran pertama kali matang gonad ikan payangka yang tertangkap menggunakan jaring insang. Informasi terkait sex ratio dapat menggambarkan keseimbangan populasi sedangkan implementasi ukuran layak tangkap dapat diduga dari ukuran pertama kali matang gonad (Hasanah et al, 2019;Mamangkey et al, 2019;Achmad et al, 2020). Sehingga dengan adanya informasi tersebut, tingkat keramahan alat tangkap jaring insang dapat deskripsikan dengan baik.…”
Section: Pendahuluanunclassified